International Conference on Security and Privacy in Communication Networks : 10th International ICST Conference, SecureComm 2014, Beijing, China, September 24-26, 2014, Revised Selected Papers, Part I - Tian, Jing.; Jing, Jiwu.; Srivatsa, Mudhakar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This 2-volume set constitutes the thoroughly refereed post-conference proceedings of the 10th International Conference on Security and Privacy in Communication Networks, SecureComm 2014, held in Beijing, China, in September 2014. The 27 regular and 17 short papers presented were carefully reviewed. It also presents 22 papers accepted for four workshops (ATCS, SSS, SLSS, DAPRO) in conjunction with the conference, 6 doctoral symposium papers and 8 poster papers. The papers are grouped in the following topics: security and privacy in wired, wireless, mobile, hybrid, sensor, ad hoc networks; network intrusion detection and prevention, firewalls, packet filters; malware, and distributed denial of service; communication privacy and anonymity; network and internet forensics techniques; public key infrastructures, key management, credential management; secure routing, naming/addressing, network management; security and privacy in pervasive and ubiquitous computing; security & privacy for emerging technologies: VoIP, peer-to-peer and overlay network systems; security & isolation in data center networks; security & isolation in software defined networking.
Security and privacy in wired, wireless, mobile, hybrid, sensor, ad hoc networks -- network intrusion detection and prevention, firewalls, packet filters -- malware, and distributed denial of service -- communication privacy and anonymity -- network and internet forensics techniques -- public key infrastructures, key management, credential management -- secure routing, naming/addressing, network management -- security and privacy in pervasive and ubiquitous computing -- security & privacy for emerging technologies: VoIP, peer-to-peer and overlay network systems -- security & isolation in data center networks -- security & isolation in software defined networking.
Keywords: Computer security; Systems and Data Security